Pengenalan Peserta Didik dan Suasana SMP/SMA Sederajat di SMP Negeri 1 Bangkinang Kota - Mimis Saputra; Astuti (Jurnal Pustaka Cendekia Pendidikan, 2025)
This article aims to review information about the Introduction of Students and the Atmosphere of Junior High Schools/Equivalent High Schools at SMP Negeri 1 Bangkinang City. The methods used are observation and interview methods. This research was conducted at SMP Negeri 1 Bangkinang City. The technical implementation of Internship I began with the preparation and briefing stage. Then continued with the implementation stage of internship I, making a final report and ending with a Seminar. The results of the study showed that the internship activity l carried out at SMPN 1 Bangkinang City for 2 months and 8 meetings, it can be concluded that SMPN 1 Bangkinang City has good integrity, both in terms of facilities and in its learning process. SMPN 1 Bangkinang City has a spacious school environment with the condition of the building used very supportive for good and conducive teaching and learning activities. The school building is equipped with sufficient classrooms and has complete facilities. The atmosphere of the school environment is full of trees so that the air around the school is good and comfortable. In addition, the location of the school is very strategic, namely close to Sadion Tuanku Tambusai Bangkinang City. SMPN 1 Bangkinang Kota has a tradition or good habits that students do every day. One of them is shaking hands every morning with the TEACHER, but now during the Covid-19 pandemic this is not done. And SMPN 1 Bangkinang Kota also has many extracurricular activities and there are many trophies from competition achievements. The facilities and infrastructure at SMPN 1 Bangkinang Kota are adequate to support smooth teaching and learning activities. SMPN 1 Bangkinang Kota also provides a place of worship that is more than just decent, namely the construction of a prayer room. Overall, this school meets good standards in the teaching and learning process.